The use of computer-aided-design (CAD) for the construction of an inertia rigid model of the ski jumper - Marques-Bruna, P.; Grimshaw, P. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Different types of isometry inertia models of the human body have been developed for the mathematical modelling of aerial movements (e.g., Yeadon, 1990). Recent advancements in rigid modelling include the use of anthropometric data adjusted for 3-dimensional (3D) simulation (Dumas et al., 2007) and of CAD in support of computational fluid dynamics projects (e.g., Meile et al., 2006). CAD may be used to model variations in flight posture and to obtain inertial parameters for the assessment of flight stability in ski jumping. Thus, this study aimed to evaluate the use of CAD for the construction of an inertia rigid model for applications in ski jumping. Methods A 14-segment 3D rigid model of the ski jumper was designed using Delcam PowerSHAPE-e 8080 CAD software, adjusted anthropometric data (Dumas et al., 2007) and postural ski-jumping data (e.g., Meile et al., 2006). Variations in flight posture included ski opening angle (SOA) at 20°, 25° and 30° and forward leaning angle (FLA) sampled from 0° to 40°, at 10° intervals. The position of the centre of gravity (CG) and the principal longitudinal moment of inertia (Iy) were computed for each posture (Parallel-axes theorem; Yeadon, 1990). Inertial properties of the helmet, boots and skis were included using equations for symmetric objects of uniform composition (Griffiths, 2006). Results The mean ± SD position of the CG for all flight postures was 54.9 ± 0.2% of athlete`s height. The mean ± SD Iy was 14.7 ± 0.3 kg • m2, where Iy decreased slightly with SOA but increased prominently with FLA. Discussion/Conclusion Iy increased noticeably with FLA; thus, FLA may be considered an important damping derivative in ski jumping that helps prevent departures from trimmed attitude. However, large FLA lowers the static stability. Drawing upon past research (Yeadon, 1990; Meile et al., 2006), CAD permitted modelling variations in flight posture and the computation of inertial parameters for the assessment of flight stability in ski jumping. References Dumas, R., Cheze, L. and Verriest, J.P. (2007). Adjustments to McConville et al. and Young et al. body segment inertial parameters. Journal of Biomechanics. 40: 543-553. Griffiths, I.W. (2006) Principles of Biomechanics and Motion Analysis. Lippincott, Williams & Wilkins. London. Meile, W., Reisenberger, E., Mayer, M., Schmölzer, B., Müller, W. and Brenn, G. (2006). Aerodynamics of ski jumping: Experiments and CFD simulations. Experiments in Fluids. 41: 949-964. Yeadon, M.R. (1990). The simulation of aerial movement - II: A mathematical inertia model of the human body. Journal of Biomechanics. 23 (1): 67-74.